Evaluation of simulation training with a stratified and intensive skill training strategy in obstetrics and gynecology - ZHANG Guo-rui, YU Xin, FAN Qing-bo, LANG Jing-he (Jichu yixue yu linchuang, 2021)
Objective This project aimed to evaluate the effect of stratified and intensive training for obstetrics and gynecology skills based on medical simulation technology. Methods The resident trainees and clinical graduates in Peking Union Medical College Hospital received stratified and intensive training of clinical skills in obstetrics and gynecology supported by medical simulation technology. Results After training, the clinical operation skill and occupational capacity of resident trainees and clinical graduates as well as the ability of self-evaluations of trainees were significantly improved. Conclusions Stratified and intensive training of clinical skills supported by medical simulation technology is a feasible and effective training method in the capacity building of residents and clinical graduates in obstetrics and gynecology.